Sender Gender Influences Emoji Interpretation in Text Messages - Butterworth, Sarah E.; Giuliano, Traci A.; White, Justin; Cantu, Lizette; Fraser, Kyle C. (Frontiers in Psychology, 2019)
With the rise in social media use, emojis have become a popular addition to text-based commu-nication. The sudden increase in the number and variety of emojis used raises questions about how individuals interpret messages containing emojis. To explore perceptions of emoji usage, we conducted a 2 (Sender Gender: Female or Male) x 2 (Emoji Type: Affectionate or Friendly) be-tween-groups experiment to examine the appropriateness and likability of each of four hypo-thetical text messages sent to a woman from either a male or female coworker. In general, we predicted that text messages containing affectionate emojis (i.e., kissing-face and heart emoji) would be perceived as more appropriate and likable when they came from female than from male senders, whereas messages containing less overtly affectionate (but still friendly) emojis (i.e., smiling-face emoji) would be considered equally appropriate and likable whether it came from female or male senders. As predicted, the results confirmed that texts with affectionate emojis were judged as more appropriate and likable when they came from women than from men. How-ever, texts with less affectionate but friendly emojis were judged as equally appropriate–but more likable–when they came from men than when they came from women. Taken together, our results indicate that gender and emoji choice influence perceptions, and therefore people should consider how emoji choice could impact the reception of their message.